Managerial Innovation in Creative Industries: Case Study of Start-Up Companies in the Archipelago - Siyamsih, Dwi (TechTalent & Business Review, 2025)
Managerial innovation plays a critical role in driving the growth and sustainability of start-ups, especially in the dynamic creative industries in Indonesia. This article explores the application of managerial innovation in the context of start-up companies operating in the creative industries sector in Indonesia, focusing on strategies and practices that have been successfully implemented. Through a case study approach, this article analyzes how these companies adapt their business models, manage change, and leverage technology to create added value. The research findings suggest that effective managerial innovation includes the use of digital technology, flexibility in project management, and the implementation of creative marketing strategies. This article also discusses the challenges faced by start-ups in implementing managerial innovation and provides recommendations for strengthening managerial practices in the creative industries. This research provides valuable insights for start-up owners and creative industry managers on how managerial innovation can enhance competitiveness and success in a competitive market.